CARTOGRAPHY OF JOY: MEETINGS BETWEEN CLOWNS AND PSYCHODRAMA - Bruhn, Marília Meneghetti (2021)
This writing proposes to share joyful encounters between the art of clowning and the sociopsychodramatic approach. The methodology adopted was cartography to accompany the process experienced in the Group of Studies and Practices in Psychology, Clowning, and Psychodrama (GEP). During the years 2017 and 2018, the GEP held monthly meetings for twelve months in which they studied and experienced the principles of these two approaches inspired by the performing arts. In the field diary reports produced with GEP, the morenian concept of spontaneity-creativity and the logic of joy present in the art of clowning stood out. Finally, the conclusion is that clowning and psychodrama are approaches that offer tools to achieve common existential goals.